Industry 5.0 : emerging paradigms for business, technology, and society - Sharma, Deergha, 1984- (CRC Press, 2025)
This book focuses on unearthing nuances of leveraging integrative and cohesive technologies in the Industry 5.0 paradigm for solving problems of business and social enterprises, which need not only be competitive but also sustain value creation for people at large. Highlights the technological evolution and its benefits to industry and society Showcases the push for industrial digitization and focuses on innovative approaches toward the human operational resilience and true sustainability objectives of Industry 5.0 Covers manufacturing, financial, marketing, and human resource techniques to resuscitate enterprises that would boost their acceptance among policymakers of multiple sectors Discusses topics such as additive manufacturing, smart manufacturing and intelligence, smart logistics, and resilient manufacturing networks Presents case studies on smart manufacturing networks, smart cities, sustainable urban development, and health monitoring systems The text is primarily written for senior undergraduates, graduate students, and academic researchers in the fields of industrial engineering, manufacturing engineering, production engineering, business management, mechanical engineering, and engineering management.
Keywords: Industry 5.0.; Technological innovations -- Management.; elektronické knihy; electronic books